2014
DOI: 10.3109/17482941.2014.889311
|View full text |Cite
|
Sign up to set email alerts
|

Duration of intra-aortic balloon pump use and related complications

Abstract: When an IABP was used for more than two days complications significantly increased. The clinical implications of the study will be strengthened if the findings are confirmed in a prospective study with a larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The incidence of IABP-related vascular complications varied widely, from 0.94% to 31.1% (mean 15.1 ± 12.5). 12 18 Only one study distinguished between early and late complications, with early complications being observed in 56 patients (11%). 15 In addition, only a small number of studies (n=5, 20%) divided vascular complications into major and minor.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of IABP-related vascular complications varied widely, from 0.94% to 31.1% (mean 15.1 ± 12.5). 12 18 Only one study distinguished between early and late complications, with early complications being observed in 56 patients (11%). 15 In addition, only a small number of studies (n=5, 20%) divided vascular complications into major and minor.…”
Section: Resultsmentioning
confidence: 99%
“…Hayıroğlu et al reported on their experience using a femoral IABP inserted percutaneously; 20% of their patients suffered from bleeding and 3% suffered from vascular injury; they did not encounter infections though this is another disadvantage of using the femoral artery as an IABP insertion site . Obviously, our patient population that is in need for long‐term IABP support is at greater risk for these complications …”
Section: Discussionmentioning
confidence: 90%
“…11 Obviously, our patient population that is in need for long-term IABP support is at greater risk for these complications. 12 While some groups have endorsed percutaneous access of the axillary artery for IABP placement, given the proximity of the brachial plexus and the extremely debilitating nature of brachial plexus injury, we prefer an "open" approach to axillary IABP placement. In our practice, axillary IABP opens a novel path of treatment for certain HF patients providing for:…”
Section: Discussionmentioning
confidence: 99%
“…12,14, 15 In contrast, longer IABP support increases vascular or hemorrhagic complications. 35 Although the absolute duration of IABP support varies strongly with institution, early insertion of IABP before end-organ dysfunction exceeds the reversible threshold, is essential. We maintained duration of IABP support at <1 week.…”
Section: Optimal Timing Of Iabpmentioning
confidence: 99%